Mobi parking navigator system (user dashboard module) - Mohd Na’imullah, Jamaludin (2013)
The using of vehicle is very important to everyone. Normally, the vehicles used to connect people from one place to another place. For example, from house want go to the workplace or shopping complex. In that case, the parking space has become costly and limited in almost for every big city in the world. In UMP Gambang Campus, the problem to get parking spaces is very difficult especially during peak hour. There is also a general problem happen in the parking spaces in front of FSKKP building, where staff and guest have to circle around the parking spaces a few times to find parking. Mobi Parking Navigator Systems was proposed and will be implementing at FSKKP office parking spaces. User Dashboard Module is web based application to assist administrator summarize the data from database. The data present using visualization technique like bar chart, pie chart, line chart, and many more. The user dashboard used to provide information about the parking area. This project use Software Development Life Cycle (SDLC) methodology to implement the development process. PHP and MySQL have been be used as programming language and database respectively for project development.